THE COMPARATIVE ANALYSIS OF GRAFT CELL SUBTYPES AND ITS CYTOKINE PRODUCTION OF LYMPHOMA AND LEUCOSIS PATIENTS - D. S. Baranova; L. V. Sakhno; I. V. Kruchkova; N. V. Pronkina; M. A. Tikhonova; E. V. Batorov; A. V. Gilevich; V. V. Sergeyevicheva; S. A. Sizikova; G. Yu. Ushakova; A. A. Ostanin; T. I. Pospelova; et al. (Acta Biomedica Scientifica, 2012)
Cell subtypes and cytokine profile of apheresis products collected from lymphoma and acute leucosis patients were analyzed. It was shown, that acute leucosis patients' grafts contained higher relative numbers of naïve T-cells, CD4+CD25high T-cells, T-lymphocytes (non-significant trend) and lower counts of granulocytes. Significant increase of relative numbers of dividing CD34+ cells (in S, G2/M phases of the cell cycle) was demonstrated, in acute leucosis patients' grafts. In lymphoma grafts the levels of CD34+ cells in G0/G1 phases were found, to be increased. Cells isolated from grafts of acute leucosis patients characterized by higher levels of proinflammatory cytokines production, such as IL-1, IL-6, MIP-1β, TNF-α, IL-8, IFN-γ (the last two ones— non-significant trend) and cytokines, essential for humoral immune response (IL-4 and — in trend — IL-10). The existing differences didn't influence on effectiveness of early lymphocyte recovery.